The classification and phylogenetic status of Jekelius (Reitterius) punctulatus (Jekel, 1866) and Jekelius (Jekelius) brullei (Jekel, 1866) (Coleoptera: Geotrupidae) using molecular data - Lobo, Jorge M.; Jiménez-Ruiz, Yolanda; Chehlarov, Evgeni; Guéorguiev, Borislav; Petrova, Yana; Král, David; Alonso-Zarazaga, Miguel Ángel; Verdú, José R. (Zootaxa, 2015)
The phylogenetic placement of Jekelius brullei (Jekel, 1866) and J. punctulatus (Jekel, 1866) (Coleoptera: Geotrupidae) was assessed using mitochondrial and nuclear molecular data to discern contrasting nomenclatural views provided by López-Colón (1996) and the Catalogue of Palaearctic Coleoptera (Löbl et al. 2006). Our results support both the monophyletic and classification status of the genus Jekelius López-Colón, 1989; and the splitting of the genus into the subgenera Jekelius López-Colón, 1989 and Reitterius López-Colón, 1996. The basal phylogenetic placement of these two species also suggests an oriental origin for Jekelius within the western Palaearctic region. Finally, we include a potential distributional map of Jekelius (Reitterius) punctulatus (Jekel, 1866) based on an exhaustive search of occurrence data.